Will casuarina glauca stress resilience be maintained in the face of climate change? - Jorge, Tiago F. (2022)
Funding Information: This work received funding support from Funda??o para a Ci?ncia e a Tecnologia (FCT), Portugal through the project PTDC/AGR-FOR/4218/2012, and the research units UID/Multi/04551/2013 (GREEN-IT), UIDB/00239/2020 (CEF) and UIDP/04035/2020 (GeoBioTec). C.A. acknowledges the FCT Investigator Program (IF/00376/2012/CP0165/CT0003). T.F.J. acknowledges FCT (PD/BD/113475/2015) and ITQB NOVA International PhD Program Plants for Life (PD/00035/2013). A.R.F. and S.A. are supported by the European Union?s Horizon 2020 research and innovation programme, project PlantaSYST (SGA-CSA No. 739582 under FPA No. 664620). Funding Information: Funding: This work received funding support from Fundação para a Ciência e a Tecnologia (FCT), Portugal through the project PTDC/AGR-FOR/4218/2012, and the research units UID/Multi/04551/2013 (GREEN-IT), UIDB/00239/2020 (CEF) and UIDP/04035/2020 (GeoBioTec). C.A. acknowledges the FCT Investigator Program (IF/00376/2012/CP0165/CT0003). T.F.J. acknowledges FCT (PD/BD/113475/2015) and ITQB NOVA International PhD Program Plants for Life (PD/00035/2013). A.R.F. and S.A. are supported by the European Union’s Horizon 2020 research and innovation programme, project PlantaSYST (SGA-CSA No. 739582 under FPA No. 664620). Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.